Analisis kecemasan matematika ditinjau dari kemampuan pemecahan masalah pada pembelajaran luring pasca pandemi - Salaamah Nur Mujahidah; Hikmatul Khusna (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
Math anxiety shows a diverse influence on mathematical problem-solving ability, based on the level of anxiety possessed. The purpose of this study is to analyze mathematical anxiety in terms of problem-solving ability in post-pandemic offline learning. This research can be classified on descriptive qualitative. The subjects of the study consisted of three students from the high, medium, and low problem-solving ability categories. Then the three subjects were given a mathematical anxiety questionnaire to analyze their anxiety levels. After that, observations and interviews related to indicators of mathematical anxiety were conducted. The results of this study described the students with high problem-solving skills had low math anxiety because not all indicators of math anxiety were met. Students with moderate problem-solving skills have high math anxiety, this is shown by the three indicators of math anxiety that are met. Students with low problem-solving skills had moderate math anxiety because students met only two of the three indicators.